Estimation of Longest Stability Interval for a Kind of Explicit Linear Multistep Methods - Y. Xu; J. J. Zhao (Discrete Dynamics in Nature and Society)
The new explicit linear three-order four-step methods with longest interval of absolute stability are proposed. Some numerical experiments are made for comparing different kinds of linear multistep methods. It is shown that the stability intervals of proposed methods can be longer than that of known explicit linear multistep methods.